Visual Screening Competencies Questionnaire (VSCQ) and orthoptic practice - Lança, Carla Costa (2012)
The identification of core competencies which are important for undertaking accurate visual screening by orthoptists is considered in this study. The aim was to construct and validate a questionnaire for orthoptists to assess visual screening competency. This study comprised three steps. The first step involved a 69-item self-assessment questionnaire constructed to assess orthoptists' perception of their competencies in visual screening programs for children. This questionnaire was constructed with statements from the Orthoptic Benchmark Statement for Health Care Programmes (Quality Assurance Agency for Higher Education, UK) and included three competency dimensions: interpersonal (IP), instrumental (IT) and systemic (ST). The second step involved questionnaire translation.